1951
DOI: 10.1161/01.cir.4.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Nitroglycerin-Flicker Fusion Response in Normal Subjects and Patients with Cardiovascular Disease

Abstract: The Krasno-Ivy nitroglycerin-flicker fusion test was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1952
1952
1961
1961

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Subsequent investigators (4, 5 , 7, 8,9,11,15) have reported that in persons free from cardiovascular disease from 21 per cent to 94 per cent of the groups investigated gave a decrease in CFF in response to the administration of nitroglycerin, while among groups of patients suffering from known cardiovascular disease from 48 to 97 per cent of them showed an increase in CFF following the administration of nitroglycerin.…”
Section: T H E Load Effect Of Nitroglycerinmentioning
confidence: 96%
“…Subsequent investigators (4, 5 , 7, 8,9,11,15) have reported that in persons free from cardiovascular disease from 21 per cent to 94 per cent of the groups investigated gave a decrease in CFF in response to the administration of nitroglycerin, while among groups of patients suffering from known cardiovascular disease from 48 to 97 per cent of them showed an increase in CFF following the administration of nitroglycerin.…”
Section: T H E Load Effect Of Nitroglycerinmentioning
confidence: 96%
“…In the literature available to us, the only mention of coarctation of the aorta in this connection concerned one case of this anomaly reported by Russek et al (17). The initial FFT was not given and the response to nitroglycerin was an increase in FFT.…”
mentioning
confidence: 96%